The effects of circadian rhythm disruption towards metabolic stress and mental health: a review - Ruthra Devi Tharumalay,; Nur Syafiqa Balqis Md. Din,; Mahadir Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This review aims to present an overview of current research findings on the possible effects of circadian rhythm (CR) disruption towards metabolic stress and mental health. CR can be described as an internal biological clock that regulates our body functions, based on our sleep/wake cycle. Any time that our normal 24-hour circadian rhythm is altered or interrupted, it will have physiological and psychological impacts. However, in today’s demanding working world, most of us are working defying the normal conditions without realising the significant drawbacks of it. Therefore, this review summarises the findings from several researches on the physiological (metabolic stress) and psychological (cognitive functioning and mental health) impacts of the CR disruption in order to assist people to have a holistic view on the effects of CR to our mind and body. Evidences that linked these aspects to health circumstances of shift workers have also been highlighted.